2021
DOI: 10.1021/acsaem.1c03025
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Electrolyte Membranes from Microporous Troger’s Base Polymers for Fuel Cells

Abstract: Fuel cells (FCs) have attracted much attention because of their high energy conversion efficiency and cleanliness. However, polyelectrolytes are a key component of FCs, and their cost and performance are not ideal at present, which is an obstacle to the development of FCs. Polymers of intrinsic microporosity (PIM) have attracted much attention as a class of membrane materials due to their three-dimensional pore structure, which can provide channels for ion transport. However, it remains challenging to prepare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…34,35 Recently, AEMs based on polymers of intrinsic microporosity (PIMs) have been widely used in many fields owing to their unique rigid contorted structure and excellent chemical stability. 2,36,37 Moreover, it is worth mentioning that the microporosity of those AEMs are beneficial for OH − transport. 38,39 Yang et al 40 has reported TB-based AEMs (named as DMBP-QTB) with V-shaped bridge structure TB units that obtained a OH − conductivity of 164 mS cm −1 at 80 °C, while the swelling ratio was 5% and the IEC value was only 0.82 mmol g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Recently, AEMs based on polymers of intrinsic microporosity (PIMs) have been widely used in many fields owing to their unique rigid contorted structure and excellent chemical stability. 2,36,37 Moreover, it is worth mentioning that the microporosity of those AEMs are beneficial for OH − transport. 38,39 Yang et al 40 has reported TB-based AEMs (named as DMBP-QTB) with V-shaped bridge structure TB units that obtained a OH − conductivity of 164 mS cm −1 at 80 °C, while the swelling ratio was 5% and the IEC value was only 0.82 mmol g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Du et al utilized a novel conductive PIM polymer based on Troger's base and used it to prepare a proton conductive membrane. 221 To impart the polymer conductivity, 4-(2-hydroxyethoxy)-1,3phenylenediamine dihydrochloride (HEPD) was introduced to the polymer backbone to form a hydrogen bond network. The resulting membrane was soaked in 1 M HCl solution for 3 h to produce a proton exchange membrane.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…These results led to other studies on TB-based AEMs. [157][158][159] In our subsequent work, we revealed the size-sieving effect of TB-based AEMs by performing diffusion dialysis experiments. [153] The DMBP-QTB membrane allowed cations with a size below 8.2 Å to diffuse quickly but retarded the passage of larger cations.…”
Section: Iems Derived From Pimsmentioning
confidence: 99%